2012
DOI: 10.3109/09513590.2011.588848
|View full text |Cite
|
Sign up to set email alerts
|

Vascular dysfunction as a cause of endometrial bleeding

Abstract: Medical therapy for HMB is limited and effective for reducing blood loss during menstruation. There is no effective treatment for the S/B associated with hormonal contraceptives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 66 publications
(87 reference statements)
0
4
0
Order By: Relevance
“…Regulation of menstrual shedding and cessation of menstrual bleeding is not fully understood. The previously proposed theory that re-epithelialization of the luminal epithelial surface is the primary factor in cessation of bleeding [73] is not supported by the histological observations that complete re-epithelialization is frequently seen on days 1 and 2 of the menses, despite continued menstrual bleeding. The stratum basalis of the endometrium maintains tissue integrity during menstrual breakdown of the stratum functionalis [5].…”
Section: Mechanisms Of Hmbmentioning
confidence: 95%
See 1 more Smart Citation
“…Regulation of menstrual shedding and cessation of menstrual bleeding is not fully understood. The previously proposed theory that re-epithelialization of the luminal epithelial surface is the primary factor in cessation of bleeding [73] is not supported by the histological observations that complete re-epithelialization is frequently seen on days 1 and 2 of the menses, despite continued menstrual bleeding. The stratum basalis of the endometrium maintains tissue integrity during menstrual breakdown of the stratum functionalis [5].…”
Section: Mechanisms Of Hmbmentioning
confidence: 95%
“…A decrease in clot strength and integrity due to the breakdown of fibrin results in an increased blood loss during menstruation. Plasminogen activators are fibrinolytic in that they induce lysis or dissolution of blood clots and endometrial and menstrual effluent levels of plasminogen activators are increased in women with excessive menstrual blood loss [73].…”
Section: Mechanisms Of Hmbmentioning
confidence: 99%
“…Several different pathways that result or cause hemostatic dysfunctions have been implicated in increased menstrual blood loss [ 30 ]. The multiple pathways include the fibrinolytic system represented by plasminogen activator and its inhibitor, increased prostaglandinE2, local cytokines, and the influx of leukocytes into the endometrial stroma.…”
Section: Clinical Findingsmentioning
confidence: 99%
“…Endometrial cytokines and metalloproteinases (MMPs) have been reported to be involved in HMB as they are initial mediators of the dissolution of endometrial collagen [ 30 ]. The proinflammatory cytokine tumor necrosis factor alpha (TNF-alpha) was significantly elevated and MMP-2 and MMP-9 were reduced in the menstrual effluent of heavy menstrual bleeders compared to women with normal bleeding [ 43 ].…”
Section: Clinical Findingsmentioning
confidence: 99%